Physical Measures to Reduce Exposure to Tap Water–Associated Nontuberculous Mycobacteria - Norton, Grant J.; Williams, Myra; Falkinham, Joseph O.; Honda, Jennifer R. (Frontiers in Public Health, 2020)
Nontuberculous mycobacteria (NTM) that cause human disease can be isolated from household tap water. Easy-to-use physical methods to reduce NTM from this potential source of exposure are needed. Filters and UV disinfection have been evaluated for their ability to reduce numbers of waterborne non-NTM organisms from drinking water, but their efficacy in reducing NTM counts are not well-established. Thus, five commercially available disinfection methods were evaluated for their potential as practical, efficient, and low-cost methods to reduce NTM from tap water. First, suspensions of tap water–adapted Mycobacterium smegmatis were passed through either a point-of-use, disposable, 7-day or 14-day Pall-Aquasafe filter. The 7-day filter prevented passage of M. smegmatis in effluent water for 13 days, and the 14-day filter prevented the passage of M. smegmatis for 25 days. Second, a granular activated carbon filter system failed to significantly reduce Mycobacterium abscessus and Mycobacterium avium numbers. Third, suspensions of tap water–adapted M. abscessus, M. avium, and M. chimaera (“MycoCocktail”) were passed through the “LifeStraw GO” hollow-fiber, two-stage membrane filtration system. LifeStraw GO prevented passage of the MycoCocktail suspension for the entire 68-day evaluation period. Finally, two different water bottle UV sterilization systems, “Mountop” and “SteriPEN,” were evaluated for their capacity to reduce NTM numbers from tap water. Specifically, MycoCocktail suspensions were dispensed into Mountop and SteriPEN water bottles and UV treated as per the manufacturer instructions once daily for 7 days, followed by a once weekly treatment for up to 56 days. After 4 days of daily UV treatment, both systems achieved a >4 log reduction in MycoCocktail CFU. After the 56-day evaluation period, suspension and biofilm-associated CFU were measured, and a >4 log reduction in CFU was maintained in both systems. Taken together, physical disinfection methods significantly reduced NTM numbers from tap water and may be easy-to-use, accessible applications to reduce environmental NTM exposures from drinking water.